PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TIMUR TAHUN 2023 BERDASARKAN FAKTOR KESEJAHTERAAN SOSIAL DAN EKONOMI KEPENDUDUKAN - Adiarsa Pramudita, Shara; Putra, Ade Ryan Isaiah; Adisty, Hilda; Wardhana, Nessa Ayu; Oktavia Rahmadani Aksa; Riefky, Muhammad (Sekolah Vokasi, Universitas Sebelas Maret, 2025)
The level of community welfare, viewed from both social and economic perspectives, reflects the overall living conditions in a region. Factors such as social dynamics, economic structure, and environmental conditions play a crucial role. As the second most populous province in Indonesia, East Java faces challenges in improving the well-being of its residents, especially given the diverse characteristics of its regions in terms of employment opportunities, education, and demographic composition. This study aims to classify the second-level administrative regions (kabupaten/kota) in East Java in 2023 based on indicators of social and economic welfare. The research utilizes secondary data sourced from the 2023 publication of BPS East Java, including indicators such as Life Expectancy, Open Unemployment Rate, Average Years of Schooling, Poverty Rate, and Labor Force Participation Rate. K-Means Clustering analysis is employed in the study. The results reveal that the second-level regions in East Java in 2023 can be grouped into three clusters: Cluster 1 represents moderately developed regions (6 members), Cluster 2 includes less developed regions (12 members), and Cluster 3 consists of the most developed regions (20 members). These findings indicate disparities in welfare levels across clusters, providing a valuable reference for policymakers to formulate region-specific development strategies and achieve targeted development goals in East Java by 2023.